Impact of substrate and bending angle on the performance of microwave PCB sensors for permittivity measurements. (April 2021) - Blazquez-Bello, Sara; Campos-Roca, Yolanda; Bangert, Axel; Sandhagen, Carl
Abstract: A design topology for a microwave planar permittivity sensor focused on manufacturing simplicity is proposed. Its operation is based on the first-notch frequency of the reflection parameter. The impacts of substrate and bending angle on the performance of this type of sensor are comparatively analyzed. Three flexible substrates are considered in comparison to three rigid ones. By full-wave electromagnetic analysis, the sensors have been simulated in contact to a material under test with a relative permittivity ranging between 1 and 20. The resulting shifts in the first-notch frequency show the potential of flexible environmentally-friendly substrates, such as liquid crystal polymer and paper, for the development of the sensors. In the flexible cases, the bending angles have been varied from 0 to 120 ∘, producing deviations in S 11 first-notch frequency of 0.4 to 4.7%. The simulation methodology is validated by experimental characterization of a prototype on Rogers 4003C laminate. Graphical abstract: Highlights: Design topology for a microwave planar permittivity sensor focused on geometrical simplicity. Comparative analysis of the impact of rigid and flexible substrates on sensor performance. Experimental validation of simulation methodology. A study on the impact of bending on flexible sensor performance based on electromagnetic analysis. Design for environmental sustainability.